Penurunan Nilai Kadar Air Dan Laju Pembakaran Pada Biobriket Limbah Kayu Sengon Dengan Variasi Tekanan - Feta Kukuh Pambudi; Wahidin Nuriana; Hantarum - (Universitas Merdeka Madiun, 2018)
Bio-briquette is a solid fuel made from organic waste and mixed with other materials and then printed using a certain pressure to get the desired shape and characteristics. This research is focused to know the influence of variation of pressure on the density, moisture content and combustion rate on the bio-briquette of sengon wood waste with variation of pressure 45 kg / cm2, 80 kg/cm2, 115 kg /cm2, 150 kg/cm2. Use of this research obtained the highest density 0.47 g/cm3 on the bacon of sengon woodÂ bio-briquette with the pressure of 150 kg/cm2, the highest moisture value is 6.6 % in the bacon of sengon wood bio-briquette with pressure 150 kg/cm2 and burning at an average of 0,35 g /min of sengon wood waste with a pressure of 150 kg /cm2. The greater the pressure the higher the density, the lower the water content and the lower the burn rate.